2010
DOI: 10.1039/c0dt00392a
|View full text |Cite
|
Sign up to set email alerts
|

DABCO-functionalized metal–organic framework bearing a C2h-symmetric terphenyl dicarboxylate linker

Abstract: A Zn-MOF assembled from a new C(2h)-symmetric terphenyl dicarboxylate and DABCO was prepared and characterized by X-ray crystallography and gas sorption analysis: a preferential sorption of CO(2) over N(2) and H(2) was observed with an exceptionally high CO(2) adsorption enthalpy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…[16] Upon CO 2 loading, Q st of Rh-PMOF-1 decreased gradually from 36 kJ mol À1 at zero loading, reaching ap lateau at approximately 24 kJ mol À1 after 0.5 mmol g À1 uptake of CO 2 . [18] The adsorption enthalpies of Rh-PMOF-1 and Ir-PMOF-1 calculated by the PM6-D3H4 method were 27.68 and 27.77 kJ mol À1 ,r espectively,w hich roughly agreed with the eventual experimental Q st . [14a, 17] The Q st curve shapes of Rh-PMOF-1 and Ir-PMOF-1 were characteristic of MOFs that possess specific CO 2 adsorption sites embedded in their pore walls, showing comparatively high Q st at low CO 2 loading, which suggested that strong CO 2 -frameworki nteractions existed in these two metalloporphyrin frameworks.…”
Section: Adsorption Propertiessupporting
confidence: 55%
“…[16] Upon CO 2 loading, Q st of Rh-PMOF-1 decreased gradually from 36 kJ mol À1 at zero loading, reaching ap lateau at approximately 24 kJ mol À1 after 0.5 mmol g À1 uptake of CO 2 . [18] The adsorption enthalpies of Rh-PMOF-1 and Ir-PMOF-1 calculated by the PM6-D3H4 method were 27.68 and 27.77 kJ mol À1 ,r espectively,w hich roughly agreed with the eventual experimental Q st . [14a, 17] The Q st curve shapes of Rh-PMOF-1 and Ir-PMOF-1 were characteristic of MOFs that possess specific CO 2 adsorption sites embedded in their pore walls, showing comparatively high Q st at low CO 2 loading, which suggested that strong CO 2 -frameworki nteractions existed in these two metalloporphyrin frameworks.…”
Section: Adsorption Propertiessupporting
confidence: 55%
“…This molecular-sieving method offers a relatively low selectivity ratio of CO 2 /N 2 , which is associated with weak interactions between the adsorbates and adsorbent. [39][40][41][42][43][44][45][46] The direct functionalization using amines could afford improved framework-amine interactions through a dative bonding scheme and secure the resultant long-term stability. These active sites include non-coordinating N or O donor atoms, [29][30][31] open metal sites, 32,33 and ions located in the frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the reaction between a Zn(II) ion and a new C 2 h -symmetric bridging ligand, 3,3"-dicarboxy-1,1′:4′,1"-terphenyl (DCT), in the presence of 1,4-diazacyclo[2,2,2]octane (DABCO) afforded a new nanoporous Zn-MOF containing DABCO ligands with an uncoordinated nitrogen atom towards onedimensional channels. The resulting DABCO-functionalized Zn-MOF showed a better adsorption of CO 2 over H 2 and N 2 with an exceptionally high CO 2 adsorption enthalpy (Gu et al, 2010 colorless crystals and the crystal structure of (I) is reported herein. In the crystal structure of the title compound the Cd atom is coordinated by four oxygen atoms of two µ 2 -coordinated DCT ligands and two oxygen atoms of two µ 1 -coordinated DCT ligands (Fig.…”
Section: S1 Commentmentioning
confidence: 98%
“…For background information on metal-organic frameworks (MOFs), see : Li & Zhou (2009) ;Huh et al (2009Huh et al ( , 2010; Youm et al (2004); Gu et al (2010).…”
Section: Related Literaturementioning
confidence: 99%